Hsp70/Bmi1-FoxO1-SOD Signaling Pathway Contributes to the Protective Effect of Sound Conditioning against Acute Acoustic Trauma in a Rat Model. (5th October 2020) - Zhu, Guoxia; Wu, Yongxiang; Qiu, Yang; Tian, Keyong; Mi, Wenjuan; Liu, Xinqin; Chen, Yuanyuan; Jia, Jinwen; Luo, Jiasheng; Lu, Lianjun; Qiu, Jianhua
Abstract : Sound conditioning (SC) is defined as "toughening" to lower levels of sound over time, which reduces a subsequent noise-induced threshold shift. Although the protective effect of SC in mammals is generally understood, the exact mechanisms involved have not yet been elucidated. To confirm the protective effect of SC against noise exposure (NE) and the stress-related signaling pathway of its rescue, we observed target molecule changes caused by SC of low frequency prior to NE as well as histology analysis in vivo and verified the suggested mechanisms in SGNs in vitro. Further, we investigated the potential role of Hsp70 and Bmi1 in SC by targeting SOD1 and SOD2 which are regulated by the FoxO1 signaling pathway based on mitochondrial function and reactive oxygen species (ROS) levels. Finally, we sought to identify the possible molecular mechanisms associated with the beneficial effects of SC against noise-induced trauma. Data from the rat model were evaluated by western blot, immunofluorescence, and RT-PCR. The results revealed that SC upregulated Hsp70, Bmi1, FoxO1, SOD1, and SOD2 expression in spiral ganglion neurons (SGNs). Moreover, the auditory brainstem responses (ABRs) and electron microscopy revealed that SC could protect against acute acoustic trauma (AAT) based on a significant reduction of hearing impairment and visible reduction in outer hair cell loss as well as ultrastructural changes in OHCs and SGNs. Collectively, these results suggested that the contribution of Bmi1 toward decreased sensitivity to noise-induced trauma following SC was triggered by Hsp70 induction and associated with enhancement of the antioxidant system and decreased mitochondrial superoxide accumulation. This contribution of Bmi1 was achieved by direct targeting of SOD1 and SOD2, which was regulated by FoxO1. Therefore, the Hsp70/Bmi1-FoxO1-SOD signaling pathway might contribute to the protective effect of SC against AAT in a rat model.